The Guidelines for Public Space Improvement of Thammasat University, Tha-prachan Campus: Spatial and Movement Network Analysis - Santad, Chulawadee (Journal of Architectural/Planning Research and Studies (JARS), 2005)
Public open spaces are significant to the urbanization of cities. Both mixed uses and users of public open spaces contribute to the liveliness of cities. [1] This is similar to the university public spaces, which play an important role in encouraging interaction among various users and activities. In addition, public spaces contribute to the academic atmosphere, which in turn, influences the quality of life of the students, staffs, and the image of the university. Presently, many problems in space usage of the Thammasat University, Tha- Prachan campus area, have been found. Some of the existing public spaces are overcrowded while many of them have been underused, neglected, and become “dead” spaces. The objective of this paper is a discussion of the overall physical aspect and the configurative structure of Thammasat University, Tha-Prachan campus area for an assessment of the characteristics of successful university public spaces. These studies will then be used in the proposal of guidelines for an improvement in other public spaces in the university. The study technique of Space Syntax [2], explored and developed by Bill Hillier of University College London, is used as a main tool in this research. Space Syntax method consists of computer modeling, which is capable of analyzing the potential of the study area through statistical spatial morphology study, and also on-site physical observations. From the configuration analysis of the University public spaces through the Space Syntax method, findings of overall university spatial characteristics are difficult to understand. These are the results of the changes in the buildings’ functions and the continued construction of new buildings without proper planning. Although public spaces in the University are almost located near potential routes, they often lack the necessary pathway connections to facilitate pedestrian accessibility. Ultimately, the study shows that successful public spaces in Thammasat University are always found in the “pocket area”, which is located within “one stepturn” of the integrators because it is easy to access and still maintains visual contact with the main circulation. On the other hand, based on the configurative analysis of the campus within its immediate urban environment, it is found that the main internal circulation is preferred by various groups of users. In conclusion, the improvements of Thammasat University, Tha-Prachan Campus’ public spaces should include an integration of potential public spaces within the larger urban context, coupled with the maintenance of visual perceptions between public spaces and circulation in order to encourage public space usage and pedestrian movement. These proposals to enrich the Tha-Prachan campus, by embracing both rigorous academic atmosphere and public activities, will undoubtedly contribute to a liberal as stated in the mission statement of the University: “to be excellent in academic, to maintain justice and to contribute to the society”.